GnRH pulse generator frequency is modulated by kisspeptin and GABA‐glutamate interactions in the posterodorsal medial amygdala in female mice. (28th October 2022) - Lass, Geffen; Li, Xiao Feng; Voliotis, Margaritis; Wall, Ellen; de Burgh, Ross A.; Ivanova, Deyana; McIntyre, Caitlin; Lin, Xian‐Hua; Colledge, William H.; Lightman, Stafford L.; Tsaneva‐Atanasova, Krasimira; O'Byrne, Kevin T.
Abstract: Kisspeptin neurons in the arcuate nucleus of the hypothalamus generate gonadotrophin‐releasing hormone (GnRH) pulses, and act as critical initiators of functional gonadotrophin secretion and reproductive competency. However, kisspeptin in other brain regions, most notably the posterodorsal subnucleus of the medial amygdala (MePD), plays a significant modulatory role over the hypothalamic kisspeptin population; our recent studies using optogenetics have shown that low‐frequency light stimulation of MePD kisspeptin results in increased luteinsing hormone pulse frequency. Nonetheless, the neurochemical pathways that underpin this regulatory function remain unknown. To study this, we have utilised an optofluid technology, precisely combining optogenetic stimulation with intra‐nuclear pharmacological receptor antagonism, to investigate the neurotransmission involved in this circuitry. We have shown experimentally and verified using a mathematical model that functional neurotransmission of both GABA and glutamate is a requirement for effective modulation of the GnRH pulse generator by amygdala kisspeptin neurons. Abstract : Modelling amygdala upstream regulation of the hypothalamic GnRH pulse generator (ARC KNDy network). (A), Optogenetic stimulation (a) of MePD Kiss1 neurones activates the GABA‐GABA disinhibitory pathway (b) reducing the inhibitory GABAergic tone arising from the MePD (c), as well as activating glutamatergic interneurones (d) projecting to the GABAergic efferents, counteracting the stimulatory output of the MePD (e) to accelerate GnRH pulse generator frequency. (B), GABA receptor antagonism in the MePD with optical stimulation of MePD Kiss1, results in net inhibition of the KNDy network to decrease pulse frequency. (C), Glutamate receptor antagonism with optical stimulation of MePD Kiss1, over‐stimulates the KNDy network resulting in a transition from a pulsatile to a quiescent dynamic state of the GnRH pulse generator.